A listening model of venture growth: entrepreneurs' listening abilities and ventures' listening capabilities - Shepherd, Dean A.; Pollack, Jeffrey M. (Journal of Business Venturing, 2025)
While we understand the importance of entrepreneurs listening to stakeholders, we lack a sufficient theory-driven understanding of why some entrepreneurs and their ventures can listen to their stakeholders more effectively than others. We offer a listening model of venture growth based on listening theories and the literatures on new ventures and capability development. Listening is initially facilitated by entrepreneurs' cognitive and behavioral processes, but continued venture growth creates a paradox for entrepreneurs. Listening to stakeholders may also deplete entrepreneurs' personal resources, diminishing their listening capacity. This paradox can be overcome by generating their ventures' listening capability—behavioral routines and attention structures for listening—enabling them to acquire and interpret quality information from stakeholders more effectively to build or adapt the capabilities necessary for venture growth. The ventures' listening capability acts as a dynamic capability, which itself can be dynamic. This listening model of venture growth contributes to the entrepreneurship literature on stakeholders, entrepreneurs' abilities, and ventures' capabilities and dynamic capabilities. Executive summary Entrepreneurs need to acquire resources from stakeholders to create and grow their ventures. Therefore, stakeholder enrollment is a critical task for entrepreneurs. The predominant research on stakeholder enrollment has been on entrepreneurs' overt behaviors to secure the support of stakeholders—a unidirectional communication pattern in which entrepreneurs communicate to audiences and stakeholders listen to and decide whether to commit their resources to ventures. However, entrepreneurs need to communicate and listen to their stakeholders. Although scholars recognize the importance of entrepreneurs listening to stakeholders, we lack sufficient understanding of why some entrepreneurs and their ventures can listen to their stakeholders more effectively than others and thus acquire and use stakeholder support critical for venture growth. Therefore, we ask, Why are some entrepreneurial actors more effective at listening to stakeholders than others? To address this question, we integrate theories of listening and the literatures on new ventures and the creation of organizational capabilities to develop a listening model of venture growth. This model explains the importance and the limitations of entrepreneurs' listening ability in acquiring and interpreting stakeholder information for venture growth. Venture members can learn from and formalize entrepreneurs' listening ability to build ventures' listening capability, which overcomes the entrepreneurs' listening limitations. Ventures' listening capability includes acquiring and interpreting stakeholder information to inform and/or change additional capabilities critical for venture growth. Specifically, the model begins with communication from stakeholders to an entrepreneur and their venture. The entrepreneur engages cognitively in listening to the stakeholders' communication and acquiring and interpreting this stakeholder information. The entrepreneur also listens behaviorally, providing back-channeling that encourages the stakeholders to share more high-quality information. The entrepreneur's listening ability can enhance and change the venture's capabilities. However, the entrepreneur's ability to notice and interpret stakeholder information is limited. Other venture members can learn the entrepreneur's cognitive and behavioral listening to represent an organizational-level listening capability. This listening capability is reflected in the venture's routines and attention structures. The venture's listening capability can build and adapt the venture's nonlistening capabilities. The venture's capabilities drive venture growth. Because the listening capability generates and enables the interpretation of more high-quality stakeholder information, the venture can use this information to change its capabilities to obtain or maintain a tight fit with a changing environment. In doing so, the venture's listening capability represents a dynamic capability—listening can change the venture's capabilities. As the venture grows, the strain on the entrepreneur's listening ability further constrains the entrepreneur as a source of information for building and adapting the venture's capabilities. Venture growth also stretches the venture's listening capability, leading to changes in this listening capability and thus building and adapting the venture's nonlistening capabilities for subsequent venture growth. Venture growth can also lead to an increase in stakeholders and, thus, more stakeholder information to be noticed and interpreted by the venture's listening capability and to adapt the venture's nonlistening capabilities if necessary. With this work, we make three primary contributions to the entrepreneurship literature: We provide theoretical insights into (1) the workings of entrepreneurs' listening ability for promoting venture growth; (2) entrepreneurs' learning from their listening ability and formalizing this ability into organizational capabilities, which is critical for information to enact nonlistening capabilities for venture growth; and (3) a venture's listening capability as a dynamic capability.